Role of Hepatectomy for Hepatocellular Carcinoma in the Era of Transplantation and Locoregional Therapy - Latchana, Nicholas; McQuinn, Christopher; Burkhart, Richard; Lahey, Samantha; Pawlik, Timothy M. (Digestive Disease Interventions, 2017)
Hepatocellular carcinoma (HCC) remains the most common primary liver neoplasm and is a leading cause of cancer-related mortality worldwide. Therapeutic options are increasing in HCC and now include surgical resection, transplantation, local ablation, directed transarterial therapies, and systemic therapies. Efficacy for each modality varies widely with the chance for cure dictated predominantly by disease biology. Surgical extirpation remains the mainstay of therapy in a curative paradigm. The role of hepatectomy and transplantation, however, has evolved as multidisciplinary management and now integrates other locoregional and systemic therapies. Herein, we review the modern approach to HCC within the context of historical trials. Studies informing a current practice that combine surgery with locoregional therapies are highlighted. A variety of transarterial options are critically examined and selection criteria for use are suggested. Finally, current best-practice guidelines are discussed with updates and practical advice where warranted.
Keywords: hepatocellular carcinoma; hepatectomy; liver transplantation; transarterial chemoembolization; transarterial radioembolization; sorafenib